2019
DOI: 10.3390/ijms20020447
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Thrombospondin-4 Correlates with Disease Severity in Osteoarthritic Knee Cartilage

Abstract: Osteoarthritis (OA) is a progressive joint disease characterized by a continuous degradation of the cartilage extracellular matrix (ECM). The expression of the extracellular glycoprotein thrombospondin-4 (TSP-4) is known to be increased in injured tissues and involved in matrix remodeling, but its role in articular cartilage and, in particular, in OA remains elusive. In the present study, we analyzed the expression and localization of TSP-4 in healthy and OA knee cartilage by reverse transcription polymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…The thrombospondin (TSP) family of large ECM glycoproteins composed of five members (TSP1-TSP5), and among them, mutations in TSP-5 (or cartilage oligomeric protein, COMP) cause human pseudoachondroplasia and multiple epiphyseal dysplasia associated with early onset OA [26]. As the roles of other TSPs for articular cartilage homeostasis are less known, Maly and colleagues investigated the expression and localization of TSP-4 in healthy and osteoarthritic human knee articular cartilage [27]. Immunohistochemistry and immunoblotting revealed that TSP-4 is present at very low level in normal articular cartilage but its ECM deposition dramatically increases in OA tissues correlating well with OA severity.…”
Section: Oa and Cartilage/subchondral Bone Extracellular Matrix Turnovermentioning
confidence: 99%
“…The thrombospondin (TSP) family of large ECM glycoproteins composed of five members (TSP1-TSP5), and among them, mutations in TSP-5 (or cartilage oligomeric protein, COMP) cause human pseudoachondroplasia and multiple epiphyseal dysplasia associated with early onset OA [26]. As the roles of other TSPs for articular cartilage homeostasis are less known, Maly and colleagues investigated the expression and localization of TSP-4 in healthy and osteoarthritic human knee articular cartilage [27]. Immunohistochemistry and immunoblotting revealed that TSP-4 is present at very low level in normal articular cartilage but its ECM deposition dramatically increases in OA tissues correlating well with OA severity.…”
Section: Oa and Cartilage/subchondral Bone Extracellular Matrix Turnovermentioning
confidence: 99%
“…Osteochondral cylinders were generated and processed as described before [39]. Samples were fixed in 4% paraformaldehyde (Sigma-Aldrich, St. Louis, MO, USA) in PBS, pH = 7.4, overnight at 4 • C. After decalcification in 10% ethylenediaminetetraacetic acid (EDTA; VWR, Osterode am Harz, Germany), samples were embedded in paraffin.…”
Section: (Immuno)histological and Immunofluorescence Staining Of Cartmentioning
confidence: 99%
“…Proteins from human cartilage samples were extracted as described previously [39]. Briefly, cartilage from areas showing different severity grades were scraped off and cut into pieces (1-3 mm 3 ), and proteins were extracted with an extraction buffer (4 M guanidine hydrochloride, 50 mM Tris, 10 mM EDTA (pH = 7.4)) overnight at 4 • C. After precipitating the proteins with 96% ethanol for 24 h at -20 • C, the protein pellet was washed and resuspended in Laemmli buffer (250 mM Tris-HCl, pH 6.8, 40% glycerol, 0.04% bromophenol blue, 8% SDS).…”
Section: Protein Extraction and Analysismentioning
confidence: 99%
See 2 more Smart Citations